2021
DOI: 10.3390/ma14143802
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Alloyed CoCrFeNiMo0.85 High-Entropy Alloy for Corrosion Resistance Coatings

Abstract: High-entropy alloys could provide a solution for corrosion resistance due to their impressive properties. Solid-state processing of high purity Co, Cr, Fe, Ni and Mo metallic powders and consolidation resulted in a bulk material that was further machined into electro spark deposition electrodes. After the stainless steel substrate surface preparation, thin successive layers of the high-entropy alloy were deposited and Pull-Off testing was performed on the newly obtained coating, for a better understanding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…From the previous analyses performed on cross-sections taken from the coated areas, it was observed that the micro cracks and pores were present on the surface of the sample, with the structure not being affected [12]. From the previous analyses performed on cross-sections taken from the coated areas, it was observed that the micro cracks and pores were present on the surface of the sample, with the structure not being affected [12].…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…From the previous analyses performed on cross-sections taken from the coated areas, it was observed that the micro cracks and pores were present on the surface of the sample, with the structure not being affected [12]. From the previous analyses performed on cross-sections taken from the coated areas, it was observed that the micro cracks and pores were present on the surface of the sample, with the structure not being affected [12].…”
Section: Resultsmentioning
confidence: 96%
“…In order to produce the CoCrFeNiMo 0.85 high-entropy coatings, the consolidated sample was machined into electrodes as presented in our previous research [12] and the coating process was conducted by using Spark Depo Model 300 (Fujieda-shi, Shizuoka-ken, Japan) electrospark deposition equipment with a miniature applicator. The shape and size of the electrodes was decided accordingly to the equipment applicator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The XRD results showed increases in μ and σ phases for the ESD-coated HEA, along with FCC and BCC phases. The microstructure of HEAs revealed that the coated HEA exhibited some pores and splats, as shown in the figure [31]. The coated HEA was homogeneous, uniform, and adhesive.…”
Section: Preparation Of Heas By Mechanical Alloyingmentioning
confidence: 93%
“…Al 0.1 CoCrFeNi alloy showed higher polarization resistance and lower corrosion rate in a molten Na 2 SO 4 -NaCl eutectic mixture at 750 ± 5 • C when compared with nickel-based alloy 718 [21]. CoCrFeNiMo 0.85 alloy used as a coating layer on stainless steel substrate could provide corrosion resistance in 3.5% NaCl solution [22].…”
Section: Introductionmentioning
confidence: 94%